Analisis Strategi Pengelolaan Sampah di Tiga Lokasi Wisata Kabupaten Banyuwangi - Eka Afrida Ermawati; Firda Rachma Amalia; Masetya Mukti (Diploma Travel Business, Faculty of Social and Political Science, Jember University, 2019)
Abstract: Trash can cause environmental problems if its existence is not handled properly. The ever-increasing garbage dump every year causes many problems to occur in the Final Disposal. This study aims to analyze the condition and distribution of waste that exist in three tourism objects in Banyuwangi, among others in Santen Island, Blimbing Sari and Beach Boom. This study uses SWOT analysis. The results of this study indicate that the cause of the distribution of waste on the beach because many people are used to throw garbage in the river so that household waste brought into the sea and the habit of littering. Although there are some bins in the tourist sites but the existence of the trash is less so functioned and less well maintained so as not to attract tourists to dispose of waste in place. Keywords: Garbage, SWOT, Banyuwangi Beach, Waste Management